Innovation - Haug, Henrike 1974- (2021)
Isaac Claesz Van Swanenburg demonstrates in his series of six paintings in the Museum Lakenhal how in the 16th century labor migration, hitherto unknown dyes that reached Europe through the establishment of a worldwide trade and new fashions changed the textile industry in Leiden.